2018
DOI: 10.3389/fsurg.2018.00050
|View full text |Cite
|
Sign up to set email alerts
|

Descending Perineum Associated With Pelvic Organ Prolapse Treated by Sacral Colpoperineopexy and Retrorectal Mesh Fixation: Preliminary Results

Abstract: Introduction and hypothesis: Descending Perineum Syndrome (DPS) is a coloproctologic disease and the best treatment for it is yet to be defined. DPS is frequently associated with pelvic organ prolapse (POP) and it is reasonable to postulate, that treatment of POP will also have an impact on DPS. We aimed to evaluate the subjective satisfaction and improvement of DPS for patients who have undergone a sacral colpoperineopexy associated with retrorectal mesh for concomitant POP.Methods: This retrospective cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…[14][15][16][17][18][19] POP causes Obstructed Defecatory Syndrome (ODS). 20,21 In our study, the mean ODS score was statistically significant between pre-operation and 3 months post-operation, also 3 months post-operation and at the time of data gathering, but there was no significant difference between pre-operation and at the time of data gathering, in mean follow up of 1 year. Thus, the ODS Altomare score was significantly improved 3 months after surgery.…”
Section: Discussioncontrasting
confidence: 47%
“…[14][15][16][17][18][19] POP causes Obstructed Defecatory Syndrome (ODS). 20,21 In our study, the mean ODS score was statistically significant between pre-operation and 3 months post-operation, also 3 months post-operation and at the time of data gathering, but there was no significant difference between pre-operation and at the time of data gathering, in mean follow up of 1 year. Thus, the ODS Altomare score was significantly improved 3 months after surgery.…”
Section: Discussioncontrasting
confidence: 47%
“…The discussion would not be complete without commenting on reports of DPS cure as part of pelvic organ prolapse surgery using 3–4 large abdominal promontofixated meshes per DPS patient ( 13 ). Based on questionnaires and telephone contact, the authors reported significant improvement for constipation, and obstructed defecation syndrome (ODS) and the need for digital maneuvers in about 60% of patients.…”
Section: Discussionmentioning
confidence: 99%